Development of simple protocols to solve the problems of enzyme coimmobilization. Application to coimmobilize a lipase and a β-galactosidase - PEIRCE, SARA; MARZOCCHELLA, ANTONIO; Virgen Ort, Jose J.; Tacias Pascacio, Veymar G.; Rueda, Nazzoly; Bartolome Cabrero, Rocio; Fernandez Lopez, Laura; Fernandez Lafuente, Roberto (RSC Advances, 2016)
This paper shows the coimmobilization of β-galactosidase from Aspergillus oryzae (β-gal) and lipase B from Candida antarctica (CALB). The combi-biocatalyst was designed in a way that permits an optimal immobilization of CALB on octyl-agarose (OC) and the reuse of this enzyme after β-gal (an enzyme with lower stability and altogether not very stabilized by multipoint covalent attachment) inactivation, both of them serious problems in enzyme co-immobilization. With this aim, OC-CALB was coated with polyethylenimine (PEI) (this treatment did not affect the enzyme activity and even improved enzyme stability, mainly in organic medium). Then, β-gal was immobilized by ion exchange on the PEI coated support. We found that PEI can become weakly adsorbed on an OC support, but the adsorption of PEI to CALB was quite strong. The immobilized β-gal can be desorbed by incubation in 300 mM NaCl. Fresh β-gal could be adsorbed afterwards, and this could be repeated for several cycles, but the amount of PEI showed a small decrease that made reincubation of the OC-CALB-PEI composite in PEI preferable in order to retain the amount of polymer. CALB activity remained unaltered under all these treatments. The combi-catalyst was submitted to inactivation at 60 °C and pH 7, conditions where β-gal was rapidly inactivated while CALB maintained its activity unaltered. All β-gal activity could be removed by incubation in 300 mM NaCl, however, SDS analysis showed that part of the enzyme β-gal molecules remained immobilized on the OC-CALC-PEI composite, as the inactivated enzyme may become more strongly adsorbed on the ion exchanger. Full release of the β-gal after inactivation was achieved using 1 M NaCl and 40 °C, conditions where CALB remained fully stable. This way, the proposed protocol permitted the reuse of the most stable enzyme after inactivation of the least stable one. It is compatible with any immobilization protocol of the first enzyme that does not involve ion exchange as only reason for enzyme immobilization. © 2016 The Royal ...